Entitlement ebook A novel. - Alam, Rumaan (2024)
NAMED ONE OF NPR’S “BOOKS WE LOVE” 2024   ONE OF THE NEW YORKER’S “BEST BOOKS WE’VE READ IN 2024” ONE OF THE WASHINGTON POST'S 50 NOTABLE BOOKS OF 2024   ONE OF KIRKUS’S “ BEST BOOK CLUB FICTION OF 2024” ONE OF REAL SIMPLE’S BEST BOOKS OF 2O24 “Rumaan Alam is a rarity... Entitlement — a psychological thriller that subtly turns into a vicious exposé of affluent liberalism— also sneaks up on you, and wins you over.”— The New York Times "A brilliant exploration of extreme wealth and how it bends the lives of those close to it... Alam keeps things crystal clear and speedway fast." — The Boston Globe “Should come with an undertow warning.” —Louise Erdrich A novel of money and morality from the New York Times bestselling author of Leave the World Behind Brooke wants. She isn’t in need, but there are things she wants. A sense of purpose, for instance. She wants to make a difference in the world, to impress her mother along the way, to spend time with friends and secure her independence. Her job assisting an octogenarian billionaire in his quest to give away a vast fortune could help her achieve many of these goals. It may inspire new desires as well: proximity to wealth turns out to be nothing less than transformative. What is money, really, but a kind of belief? Taut, unsettling, and alive to the seductive distortions of money, Entitlement is a riveting tale for our new gilded age, a story that confidently considers questions about need and worth, race and privilege, philanthropy and generosity, passion and obsession. It is a provocative, propulsive novel about the American imagination.